The Role of Community Nurses to Prevent Domestic Violence During the Covid-19 Pandemic - Arnindya Kanti Prasasti; Widyatuti Widyatuti (Global Health Science Group, 2021)
Social restrictions policies to control Covid-19’s transmissions creates new problems. Higher stressors caused by childcare, work, financial, and health with lack access to entertainment and social support cause increasing of domestic violence. Domestic violence triggers physical and mental health problems. Nurses as health workers in community has some important roles to prevent this problems. This literature review is to describe the phenomenon of domestic violence and explain the role of nurses in reducing domestic violence during the Covid-19 pandemic. The keywords used in searching for articles are Covid-19, nurse, role, pandemic, preventing, maltreatment, and domestic violence so that 15 articles obtained and 11 articles (from 2017-2021), from several reputable online journal databases such as ClinicalKey, EBSCO, Proquest, Sage Publications, Science Direct, Scopus, SpringerLink, Taylor & Francis, and Willey Online. Articles analysis is carried out using the narrative literature review methods. ommunity nurses play important roles as care providers, educators, managers, collaborators, advocates, and leaders, to prevent domestic violence during pandemic. Community nurses in preventing domestic violence experience several obstacles, such as lack of home visit due to the pandemic, a lack of understanding of community nurses about domestic violence, and the community's perception that violence is the family’s privacy.